Trend Revolusi Industry 4.0 : Peran media pembelajaran - Maulidina Tamalla; Indah Setyo Wardhani (Pendikdas: Pendidikan Dasar, 2024)
Choosing the right learning media in the era of the industrial revolution 4.0 is important. This is done so that learning is able to answer the challenges of the industrial revolution 4.0. This research aims to describe learning media and the challenges of the industrial revolution 4.0. The research method used is a literature study, namely reviewing based on or several sources of books, articles or journals. The results of the research are in the form of a description of learning media in the era of the industrial revolution 4.0. Implementation of research in the form of applicability of research results as a reference in choosing the right learning media in the era of the industrial revolution 4.0.